Facilitators and impediments in the adoption and implementation of the HubSpot marketing automation system - Leinonen, Miira (2017)
Marketing automation is growing popularity among companies but it has not yet received great academic interest. Therefore, neither marketing automation systems have been studied thoroughly. Other preceding systems in marketing and sales, such as customer relationship management (CRM) and sales force automation (SFA) have however been explored comprehensively.